2021
DOI: 10.1186/s40364-021-00262-3
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA APCDD1L-AS1 induces icotinib resistance by inhibition of EGFR autophagic degradation via the miR-1322/miR-1972/miR-324-3p-SIRT5 axis in lung adenocarcinoma

Abstract: Background Epidermal growth factor receptor-tyrosinase kinase inhibitor (EGFR-TKI) resistance is the major obstacle in the treatment of lung adenocarcinoma (LUAD) patients harboring EGFR-sensitive mutations. However, the long non-coding RNAs (lncRNAs) related to EGFR-TKIs resistance and their functional mechanisms are still largely unknown. This study aimed to investigate the role and regulatory mechanism of lncRNA APCDD1L-AS1 in icotinib resistance of lung cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Ferroptosis is an iron-dependent cell death program that has been shown to be involved in the development of tumors and the response to antitumor treatment (14,19,41). In addition, many lncRNAs are known to participate in malignant tumor progression and tumor resistance, and become new biomarkers and therapeutic targets for cancer diagnosis and treatment (42)(43)(44). Many lncRNAs can affect the ferroptosis of cancer cell and tumor immunity (45)(46)(47), being promising to become tumor markers with clinical value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroptosis is an iron-dependent cell death program that has been shown to be involved in the development of tumors and the response to antitumor treatment (14,19,41). In addition, many lncRNAs are known to participate in malignant tumor progression and tumor resistance, and become new biomarkers and therapeutic targets for cancer diagnosis and treatment (42)(43)(44). Many lncRNAs can affect the ferroptosis of cancer cell and tumor immunity (45)(46)(47), being promising to become tumor markers with clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A11, the target gene of lncRNA, is a key gene of ferroptosis that can be downregulated by XAV939 (an NSCLC inhibitor), which inhibits the development of NSCLC through a ferroptosis mediated pathway (49). Jie Wu et al found that lncRNA APCDC1L-AS can induce LUAD resistance to icotinib (a kind of TLIs) by inhibiting autophagic degradation of EGFR (44). The lncRNA P53RRA in the cytoplasm affects some metabolic gene transcription and promotes ferroptosis by activating P53 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Wu (2021) Exosomal-mediated transfer of APCDD1L-AS1 induces 5-fluorouracil resistance in oral squamous cell carcinoma via miR-1224-5p/nuclear receptor binding SET domain protein 2 (NSD2)
…”
mentioning
confidence: 99%
“…However, with the deepening of the research, it has been confirmed that lncRNAs are crucial to biological development and disease occurrence, including mediating cell proliferation, differentiation, apoptosis, autophagy, drug resistance, etc. (Bhat et al, 2020;Huang et al, 2021;Wu et al, 2021). Of special note, lncRNAs also affect the proliferation and migration of VSMCs and then participate in vascular diseases.…”
Section: Discussionmentioning
confidence: 99%